Vinyl carbonate photopolymers with improved mechanical properties for biomedical applications. Issue 5 (3rd July 2016) - Mautner, Andreas; Steinbauer, Barbara; Russmüller, Günter; Lieber, Roman; Koch, Thomas; Stampfl, Jürgen; Liska, Robert
Abstract: Recently, vinyl carbonates have been demonstrated to be a versatile alternative to acrylates and methacrylates in biomedical applications as they exhibit photoreactivity and mechanical properties on a level or even above (meth)acrylates. Furthermore, much lower cytotoxicity as well as degradation via a surface erosion mechanism qualify them for medical use. However, it is highly desirable to improve the mechanical properties of vinyl carbonates to reach the performance of PLA. Thus, the main focus of this study lies on designing vinyl carbonates with suitable functional groups that are capable of augmenting mechanical properties of vinyl carbonates, e.g. cyclic structures or urethane groups, and implementing them into the vinyl carbonate structures. Resulting monomers were tested regarding their photoreactivity and cytotoxicity. Furthermore, cured specimens were investigated concerning their mechanical properties. In addition, the thiol-ene reaction was utilized to further improve photoreactivity. The new vinyl carbonates exhibit excellent biocompatibility and photoreactivity that can be significantly enhanced through the addition of thiols onto the level of highly photoreactive acrylates. Most importantly, results showed that the mechanical properties could be improved onto the level of PLA and above.